Strategies for Digital Economy in Supporting the Transformation of the Cultural and Tourism Industry - Wang, Shaojie (International Journal of Global Economics and Management, 2024)
The former Ministry of Culture clearly stated in the "Guiding Opinions on Promoting the Innovative Development of the Digital Cultural Industry" that the tourism industry should move towards digitalization. Against this backdrop, this paper aims to explore feasible strategies for the digital economy to assist in the transformation of the cultural and tourism industry. The study adopts literature research, theoretical analysis, and practical investigation methods. It first briefly explains the relevant concepts of the digital economy and the transformation of the cultural and tourism industry, then analyzes the internal mechanisms of how the digital economy supports the transformation of the cultural and tourism industry under the current situation, and finally discusses the strategies in detail.